2020
DOI: 10.1080/03054985.2020.1781607
|View full text |Cite
|
Sign up to set email alerts
|

Student loans and participation in postgraduate education: the case of English master’s loans

Abstract: Higher education researchers have paid little attention to postgraduate participation. This issue has become more prominent in England following the introduction of high undergraduate fees. Many predicted that master's participation would decline consequently, strengthening known inequalities in access by socio-economic background at master's level. The introduction of master's loans in 2016/17 intended to help those without access to independent resources afford master's study. We investigate whether this int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Following the extension of student loans to master's level, it would also appear that, compared with earlier transitions, social class differences in postgraduate progression substantially reduce, suggesting the appearance of 'meritocratic' progression. Previous research by (Mateos-González & Wakeling, 2020) has shown that the introduction of master's loans in England has widened the participation of less well-off students in postgraduate education. Indeed, some disadvantaged groups have marginally higher rates of progression than their more advantaged counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Following the extension of student loans to master's level, it would also appear that, compared with earlier transitions, social class differences in postgraduate progression substantially reduce, suggesting the appearance of 'meritocratic' progression. Previous research by (Mateos-González & Wakeling, 2020) has shown that the introduction of master's loans in England has widened the participation of less well-off students in postgraduate education. Indeed, some disadvantaged groups have marginally higher rates of progression than their more advantaged counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Except for the well-known tax revenue, student loans are ignored by most people as income. According to data from Student Loan Corporation (SLC) [17], in 2017, 73% of EU international students can apply for student loans, and 94% of local students in the UK can apply for student loans. Compared with British students, it is more complicated for EU students to apply for student loans.…”
Section: 2fiscal Impactsmentioning
confidence: 99%
“…The novel coronavirus pandemic has brought challenges to the training of graduate students. According to the spirit of the epidemic prevention and control documents, university departments have taken various measures at the same time and implemented the work of graduate students during the epidemic period through online platforms, including online course teaching, online scientific research guidance, online dissertation defense, etc [8]. Cloud guidance, while solving the problems brought by the epidemic, also makes our postgraduate guidance much more convenient.…”
Section: Introductionmentioning
confidence: 99%